PERANCANGAN CORPORATE IDENTITY DALAM MEMBANGUN CITRA PADA LAUNDRY TITU BINATU SEMARANG - OfaKinestuRilta Ofa; Aris Sarwo Nugroh; Nuris Dwi Setiawan (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The development of the laundry business requires an effective visual communication strategy to build brand image and competitiveness. This study aims to design a visual branding strategy for Titu Binatu, a laundry UMKM in Tembalang, Semarang. Through a visual communication design approach, this study analyzes visual identity elements such as logos, colors, typography, and promotional media in shaping consumer perceptions. The method used is qualitative through observation, interviews, and literature studies. The results show that Titu Binatu needs a strong visual identity and appropriate promotion to reach the market, especially students and workers. Strengthening branding with offline and online media is needed so that visual branding becomes a strategic tool in business development in the digital era.